Effects of rhythm changes on sprint speed and step rate in women`s 400 m hurdles - Hase, S.; Iso, S. (European Journal of Human Movement, 2025)
The 400 m hurdles are considered a highly strategic event, where the step strategy (e.g. step switching (SS)) during the race has a significant effect on performance. However, many studies have focused on men's 400 m hurdles, and fewer studies are available on the women`s equivalent. Therefore, the purpose of this study was to determine the effects on sprint speed and step rate before, during, and after SS in Japanese women`s 400-m hurdle races. Data from 41 races of 19 Japanese athletes were analyzed. Race data were obtained from publicly available internet broadcasts. A one-way repeated measures ANOVA and post-hoc analyses were used to compare the step rate with three sections (before, during and after step switching). The step rate was found to be significantly higher during SS compared with both before and after SS (p < 0.05). The rate of change in sprint speed was significantly higher during SS than after SS (p < 0.001). These results indicate that SS contribute to stalling during women`s 400 m hurdle races, which might be a strategy that significantly influences performance.